Step-by-Step Teaching Model of Batik Art in Practical Lessons - Kenjayeva Umida Rajabovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ABSTRACT: This article examines a step-by-step teaching model for batik art in practical lessons, focusing on its effectiveness in developing students’ artistic skills, creativity, and technical competence. Batik, a traditional wax-resist dyeing technique, requires careful planning, patience, and sequential learning to master. The proposed model outlines a structured approach that guides students through each stage of the batik process, from pattern design and wax application to dyeing and finishing. The study highlights the pedagogical benefits of this stepwise method, including improved skill acquisition, enhanced understanding of artistic principles, and increased student engagement. Additionally, the article explores how this model supports individualized learning, fosters problem-solving abilities, and encourages reflective practice, making it an effective tool for art educators in developing both technical and creative competencies.